Peranan Aparatur Desa Dalam Pencegahan Kenakalan Remaja - Eko Gani PG (Asia-Pacific Journal of Public Policy, 2019)
Adolescence is a time of experiencing many changes in body, spirit, and mind. At this time, adolescents experience a lot of emotional turmoil and problems which are generally caused by social conflicts. In this study, the researcher used a descriptive qualitative approach, and the data were collected through observation, interviews, and documentation. The purpose of this study was to determine the efforts of village officials and the obstacles in preventing juvenile delinquency at a village in the Aceh province. The form of delinquency that is often carried out by adolescents in the village namely lying, leaving without saying to their parents and having no clear purpose as well as causing negative actions, skipping school (leaving school/not attending school without the awareness of the school), promiscuity/immoral acts (watching pornographic films), theft (the activity of taking other people's belongings), illegal racing/sounding the sound of a bicycle motor big. The causes of adolescent delinquency in this village include; (1) internal factors- an identity crisis and weak self-control, and (2) external factors - family, education, community, religion, and technology.